2021
DOI: 10.1038/s41598-020-80042-5
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-level differences between brain parenchymal- and cerebrovascular-seeded Aβ fibrils

Abstract: Alzheimer’s disease is characterized by neuritic plaques, the main protein components of which are β-amyloid (Aβ) peptides deposited as β-sheet-rich amyloid fibrils. Cerebral Amyloid Angiopathy (CAA) consists of cerebrovascular deposits of Aβ peptides; it usually accompanies Alzheimer’s disease, though it sometimes occurs in the absence of neuritic plaques, as AD also occurs without accompanying CAA. Although neuritic plaques and vascular deposits have similar protein compositions, one of the characteristic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…The switching mechanism is more likely to be dominated by the filament formation mechanism based on our preliminary material characterization results of the switching material and also the detailed analysis of the bipolar switching curve. The fundamental resistive switching phenomenon of VCM metal oxide materials is explained by the formation and rupture of conductive filaments constructed by oxygen vacancies, defects, ion migration between electrodes through the grain boundaries, and so on [ 18 , 36 , 37 , 38 ]. Hsu et al (2012) reported resistive switching through oxygen vacancy filament formation in a core–shell Au/Ga 2 O 3 single nanowire, though a low density of oxygen vacancies in the Ga 2 O 3 shell was perceived.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The switching mechanism is more likely to be dominated by the filament formation mechanism based on our preliminary material characterization results of the switching material and also the detailed analysis of the bipolar switching curve. The fundamental resistive switching phenomenon of VCM metal oxide materials is explained by the formation and rupture of conductive filaments constructed by oxygen vacancies, defects, ion migration between electrodes through the grain boundaries, and so on [ 18 , 36 , 37 , 38 ]. Hsu et al (2012) reported resistive switching through oxygen vacancy filament formation in a core–shell Au/Ga 2 O 3 single nanowire, though a low density of oxygen vacancies in the Ga 2 O 3 shell was perceived.…”
Section: Resultsmentioning
confidence: 99%
“…This process is also recognized as trap-controlled SCLC (TC-SCLC). As the applied bias voltage crosses the voltage called the trap-filled limited voltage (V TFL ), the I–V curve corresponds to the trap-free SCLC (TF-SCLC) [ 19 , 37 ]. During this period, all the traps are filled, and the excess electrons are free to conduct electricity between electrodes, so the conductive filament is formed to produce an LRS state.…”
Section: Resultsmentioning
confidence: 99%
“…Magic angle spinning (MAS) solid-state NMR is not limited by molecular correlation times and is particularly useful to study large protein complexes, amyloid fibrils, and membrane proteins. With the sensitivity gains conferred by dynamic nuclear polarization (DNP), MAS NMR has the sensitivity to detect proteins at their endogenous concentrations in complex biological environments. ,,, However, the effectiveness of DNP-enhanced MAS NMR is critically dependent on sample composition and experimental conditions. , DNP increases the sensitivity of NMR spectroscopy through the transfer of the large spin polarization of an unpaired electron to nearby nuclei which are typically introduced into a sample by doping with millimolar concentrations of stable biological radicals. In addition to millimolar concentrations of polarizing agents, a typical DNP sample of a hydrated biomolecule is cryoprotected by the addition of 60% d 8 -glycerol to aid in the formation of vitreous ice, deuterated to ∼90% to aid spin diffusion, frozen to near liquid nitrogen temperatures, and subjected to magic angle spinning. Pioneering work applying DNP MAS NMR to cultured mammalian cells suggested that measurement of low concentrations of proteins inside mammalian cells is possible, but uncertainty about the biological integrity of the cellular sample limits the utility of the structural information for in-cell experiments.…”
Section: Introductionmentioning
confidence: 99%
“…ssNMR has been used extensively on amyloid proteins associated with diseases, including AD, PD, HD, systemic amyloidosis, and prion diseases ( 93 , 97 ). However, these generally have been synthetic or in vitro studies ( 91 ).…”
Section: Ssnmr: a Whole-structure Viewmentioning
confidence: 99%